2022
DOI: 10.1029/2021ms002926
|View full text |Cite
|
Sign up to set email alerts
|

An Online‐Learned Neural Network Chemical Solver for Stable Long‐Term Global Simulations of Atmospheric Chemistry

Abstract: Global modeling of atmospheric chemistry is a grand computational challenge due to the large number of coupled chemical species, the nonlinearity and numerical stiffness of chemical mechanisms, and the interactions with transport on all scales. The U.S. National Research Counci's National Strategy for Advancing Climate Modeling identifies atmospheric chemistry as a priority frontier for Earth System Model (ESM) development (National Research Council, 2012). Current atmospheric chemistry models integrate the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Maintaining numerical stability with the use of emulators for atmospheric chemistry and other atmospheric parameterizations is a known issue and initial steps have been taken to address it (Brenowitz & Bretherton, 2018;Kelp et al, 2020Kelp et al, , 2022. These recent studies found some performance improvements by using a "recurrent training" scheme, where a model was rolled out in time for n time steps during training, and a loss was calculated on Note.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining numerical stability with the use of emulators for atmospheric chemistry and other atmospheric parameterizations is a known issue and initial steps have been taken to address it (Brenowitz & Bretherton, 2018;Kelp et al, 2020Kelp et al, , 2022. These recent studies found some performance improvements by using a "recurrent training" scheme, where a model was rolled out in time for n time steps during training, and a loss was calculated on Note.…”
Section: Discussionmentioning
confidence: 99%
“…It could be implemented as is into a 3D model with an operator splitting method: transport, advection, etc,̇ that are solved with traditional ODE solvers and the chemistry is solved with the GRU. This is, for instance, the approach adopted by Keller and Evans (2019) for solving ozone chemistry with random forests in GEOS-Chem and by Kelp et al (2022) with MLPs.…”
Section: Incorporation Of ML Models Into 3d Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning (ML) approaches are an emerging technique for decreasing the computational burden of earth system models with more e cient ML parameterizations, but have documented challenges such as unstable error growth and physical inconsistency which can happen when predicted recurrently (Kelp et al, 2018) or when interacting with other processes in the context of larger models (Rasp et al, 2018;Brenowitz & Bretherton, 2019). One approach towards ML models that can stably interact with other model processes is online training: parameter optimization of ML surrogates while running the entire model (Rasp, 2020;Kelp et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They implemented it in GEOS-Chem (Kelp et al, 2022), achieving stable one-year simulations for ozone prediction with less than 10 % bias compared to the reference and reducing computational times by a factor of five. The motivation of these previous studies stems from reducing the costs of calculating chemistry, that is usually taking from 50 % to 90 % of the computational costs of running global chemistry models such as GEOS-Chem (Keller & Evans, 2019).…”
Section: Introductionmentioning
confidence: 99%